Pengaruh Paritas dan Nutrisi Terhadap Kejadian Blighted Ovum Pregnancy - Rahmawati, Dechoni; Dewi Anggraeni, Fatimah (Universitas Muhammadiyah Klaten, 2022)
According to data from the World Health Organization (WHO), the percentage of possible abortion is quite high, around 15-40%. In Indonesia, it is estimated that there are 500,000-750,000 abortions. Blighted ovum is a state of the product of conception that does not contain a fetus. It is estimated that worldwide Blighted ovum is 60% of the causes of miscarriage cases, in ASEAN (association of Southeast Asian Nations) it reaches 51%, in Indonesia it is found 37% of every 100 pregnancies, in Yogyakarta Province it reaches 30% of 100 pregnancies and in Sleman Regency. as much as 43.39% (WHO, 2015). The incidence rate at PKU Muhammadiyah Gamping shows an increase in the Blighted ovum rate during the last 3 years in 2016 as much as 6.02%, in 2017 it increased by 6.05%, and in 2018 it increased by 6.06% (Kemenkes RI, 2018). Mothers who experience abortions due to blighted ovum have characteristics including age, parity, nutrition and gestational spacing, in addition, age, parity, nutrition and gestational spacing are also factors that cause blighted ovum. Objective: To identify the factors that influence the incidence of blighted ovum pregnancy. Research Methodology: This type of research is analytical observational with a cross-sectional approach. The location of this research is PKU Muhammadiyah Gamping Yogyakarta with a sample of 30 respondents and the sampling technique is Simple Random Sampling. The data analysis technique used in this research is chi square. Research Results: Factors related to the incidence of blighted ovum pregnancy are parity factors as indicated by a p-value of 0.004 where the p-value is smaller than the significance value with an error rate of 5% (0.05). This shows that there is a relationship between the parity variable and the incidence of blighted ovum pregnancy. For the nutrition variable, the p-value is 0.151 where the p-value is greater than the significance value with an error rate of 5% (0.05). This shows that there is no relationship between nutritional variables and the incidence of blighted ovum pregnancy.